Android Application USB-Serial datalogger for embedded systems - Figueroa-Mosquera, Nícolas Francisco (2016)
This article shows the application made in Android that enables the registration of the data obtained by serial communication from any embedded system, as well as the testing of the inputs and outputs in a portable device equipped with the Android operating system. To achieve this, the Ohwada libraries were used as reference, modified so that the register option in the SD memory of the mobile device was available from the moment the start button is pressed until the moment the stop button is pressed. The way of showing the acquired values by serial in a single console was also modified, along with some configurations parameters in the transmission of data.